2018
DOI: 10.1371/journal.pone.0204281
|View full text |Cite
|
Sign up to set email alerts
|

Low-volume goat milk transmission of classical scrapie to lambs and goat kids

Abstract: The risk of classical scrapie transmission in small ruminants is highest during the neonatal period with the placenta recognized as a significant source of infection. Milk has also been identified as a source of scrapie with sheep-to-sheep transmission occurring after neonatal consumption of as little as 1–2 liters of milk; concurrent mastitis due to small ruminant lentivirus (SRLV) infection may be associated with increased scrapie transmission via milk in sheep. In contrast, goat-to-sheep transmission has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Sheep and goats are typically thought to be infected with scrapie as lambs or kids via contact with the placenta or placental fluids. However, evidence suggests that both sheep and goats can be infected from ingestion of prions shed in bodily fluids [e.g., milk (1)(2)(3)(4)(5)(6), saliva (7), and feces (8)] and contaminated environments (9,10), such as pastures. Animals that may be shedding the scrapie agent and are asymptomatic are rarely identified until the onset of clinical signs, substantially increasing risk of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep and goats are typically thought to be infected with scrapie as lambs or kids via contact with the placenta or placental fluids. However, evidence suggests that both sheep and goats can be infected from ingestion of prions shed in bodily fluids [e.g., milk (1)(2)(3)(4)(5)(6), saliva (7), and feces (8)] and contaminated environments (9,10), such as pastures. Animals that may be shedding the scrapie agent and are asymptomatic are rarely identified until the onset of clinical signs, substantially increasing risk of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Studies estimated that the main sources of environmental contamination in classical scrapie disease are placentas [ 94 , 95 , 96 ], feces [ 97 ], and carcasses of infected animals [ 98 ]. Research demonstrated that the prion protein is also eliminated through excretions (feces and urine) or secretions (milk and saliva) [ 66 , 97 , 99 , 100 , 101 , 102 , 103 , 104 ] and semen [ 105 ].…”
Section: Pathogenesis and Transmission Of The Diseasementioning
confidence: 99%
“…The presence of PrP Sc in the mammary glands of co-infected scrapie animals with maedi-visna [ 181 ] suggested that milk could serve as a potential transmission vehicle of scrapie. In addition, the presence of PrP Sc in the distal ileum and rectal mucosa from lambs with susceptible genotypes fed with milk from scrapie-affected females demonstrated the transmission of the disease through this route [ 66 , 99 , 100 ].…”
Section: Infectivity Of the Different Tissuesmentioning
confidence: 99%
“…CS transmits horizontally, under field conditions, due to the ingestion of PrP Sc either directly from secreta/excreta from infected animals, most notably the presence of PrP Sc in the placenta of infected sheep and goats (Tuo et al., 2002 ; Schneider et al., 2015 ), via milk (Konold et al., 2008 , 2013; Madsen‐Bouterse et al., 2018 ), or via environmental contamination with such infected materials (Touzeau et al., 2006 ; Dexter et al., 2009 ; Konold et al., 2015 ).…”
Section: Assessmentmentioning
confidence: 99%